Knots, spoons, and cloches: DNA barcoding unusual larval forms helps document the diversity of Neotropical marine annelids. Issue 2 (29th January 2021) - Collin, Rachel; Venera‐Pontón, Dagoberto E.; Macdonald, Kenneth; Driskell, Amy C.; Boyle, Michael J.
Abstract: The morphological diversity of marine annelid larvae is stunning. Although many of the larval forms have been categorized as trochophores or modified trochophores, there are a few groups with distinctive larval features that make them easy to distinguish from other annelid larvae. We collected 252 annelid larvae from the plankton, with particular emphasis on oweniids, polygordiids, and thalassematids (i.e., echiurans) and sequenced fragments of their cytochrome c oxidase subunit 1 and 16S ribosomal RNA genes. We found six oweniid, five polygordiid, and eight thalassematid OTUs. Thalassematids were found only in samples from the Pacific, and oweniids were found only in Caribbean samples. Among the oweniids we found two distinct morphotypes, one with a narrow, cloche shape and another that had a wider and more rectangular shape with clearly developed lappets. Among the polygordiids, we identified one larva as Polygordius eschaturus and several larvae as Polygordius jenniferae . All larvae, except for the P. eschaturus, which was at a stage too early to make a determination, were endolarvae. Among the thalassematids, we identified larvae of Ochetostoma edax and found seven unidentified OTUs. Finally, 150 miscellaneous polychaete larvae were sequenced, representing ~76 OTUs. Four rostraria larvae from the Caribbean, whose sequences confirm the long‐held assumption that they are amphinomids, could not be identified to species. In total only 5% of these OTUs could be identified to species with known sequences, and most could not be identified to genus or even family with reasonable certainty. It is clear that this poor coverage in the reference databases will limit metabarcoding efforts to document numbers of OTUs, and that DNA barcodes will be of limited use for identifying neotropical marine annelids until reference databases have improved their coverage of this group.